1986
DOI: 10.1002/jlb.40.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Model for Leukocyte Regulation by Chemoattractant Receptors: Roles of a Guanine Nucleotide Regulatory Protein and Polyphosphoinositide Metabolism

Abstract: Binding of chemoattractants to their receptors on phagocytes activates a guanine nucleotide regulatory (N) protein through the substitution of GTP for GDP on N. The activated N protein in turn stimulates a membrane-associated phospholipase C by lowering the Ca2+ concentration required to activate this enzyme from supraphysiologic levels to ambient intracellular concentrations. The phospholipase C hydrolyzes phosphatidylinositol 4,5-bisphosphate into the Ca2+ mobilizer inositol 1,4,5-trisphosphate and the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(52 citation statements)
references
References 89 publications
3
49
0
Order By: Relevance
“…CXCR2 bound both IL-8 (K d ϭ 2.4 Ϯ 1.3 nM; B max ϭ 8460 Ϯ 232 receptors/cell) and GRO␣ (K d ϭ 1.9 Ϯ 0.9 nM; B max ϭ 7895 Ϯ 637 receptors/cell) with similar affinities. The K d were similar to that of CXCR2 expressed in 3ASubE cells (3.1 nM) (10), HEK 293 cells (4 nM) (21) or the native receptors in neutrophils (ϳ1-2 nM) (26). Upon IL-8 ( Fig.…”
Section: Resultssupporting
confidence: 60%
“…CXCR2 bound both IL-8 (K d ϭ 2.4 Ϯ 1.3 nM; B max ϭ 8460 Ϯ 232 receptors/cell) and GRO␣ (K d ϭ 1.9 Ϯ 0.9 nM; B max ϭ 7895 Ϯ 637 receptors/cell) with similar affinities. The K d were similar to that of CXCR2 expressed in 3ASubE cells (3.1 nM) (10), HEK 293 cells (4 nM) (21) or the native receptors in neutrophils (ϳ1-2 nM) (26). Upon IL-8 ( Fig.…”
Section: Resultssupporting
confidence: 60%
“…A mechanism involving both membrane potential and short range diffusion might account for these observations. One likely participant is inositol 1,4,5-triphosphate, which is generated during FMLP stimulation of neutrophils (54). Inositol 1,4,5-triphosphate promotes Ca 2ϩ release from the ER, which in turn triggers store-operated Ca 2ϩ influx across the plasma membrane (55).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that IGF-I is chemotactic for resting and activated human T lymphocytes with a half-maximal concentration consistent with the Kd of the receptor, providing evidence that the effect shown is mediated via high-affinity IGF-I receptors. In addition, the gradient-enhanced motility (chemotaxis) and high-dose inhibition demonstrated resemble that seen with insulin (20), , and with other receptor-mediated chemotaxis models such as N-formylated-methionyl peptides for neutrophils (36,37) and platelet-derived growth factor for neutrophils and monocytes (38,39). However, the precise mechanism through which IGF-I enhances T cell motility is unclear.…”
Section: Discussionmentioning
confidence: 92%